A technical approach to equity investing in South Africa: A tale of two indexes - Massoud Metghalchi; John Kagochi; Linda Hayes (Cogent Economics & Finance, 2021)
This research uses Simple Moving Averages and four other well-known indicators to investigate the usefulness of the Technical Analysis approach to the Johannesburg stock exchange (JSE) in South Africa. Technical indicators are applied to two JSE indexes representing large cap and small cap companies over the period of 1/2/2002 to 12/31/18. The best trading rules for both the Small Cap and All Share indexes involve the use of two simple moving averages. For the Small Cap Index, our best two trading rules and a low-risk strategy have positive annual net excess return over the Buy and Hold (B&H) strategy for the entire period and each sub-period, thus trading rules can beat the B&H strategy. However, we cannot say the same for the All Share Index (representing large cap companies).
Keywords: G1; G12; 330; efficient market hypothesis; trading indicators; trading rules